ANALISIS KINERJA KEUANGAN KOMPARATIF KOPERASI UNIT DESA (KUD) TUNAS MUDA, KUD KARYA MAJU DAN KUD TANDAN MAS JAYA DI KECAMATAN DAYUN KABUPATEN SIAK - Tri Puji Aswoko; Ahmad Rifai; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this study is to analyze the financial performance comparison cooperation Tunas Muda, Cooperation Karya Maju, and Cooperation Tandan Mas Jaya during the 2008-2010 period. Financial performance measured by financial ratio analysis. The results obtained of financial performance that Cooperation Tunas Muda and Cooperation Tandan Mas Jaya is liquid with a current ratio and the quick ratio is more than one, while the Cooperation Karya Maju has more than one current ratio and the quick ratio is less than one. The analysis shows that the solvency ratio Cooperation Tandan Mas Jaya in the state of solvability by the debt to assets and debt to equity obtained more than one, while the Cooperation Tunas Muda and Cooperation Karya Maju not sovabel because it has a debt to equity ratio is less than one. Cooperation ability to generate profits from assets obtained that Cooperation Tandan Mas Jaya larger than the Cooperation Karya Maju and Larger than Cooperation Tunas Muda. However, the profitability of own capital Cooperation Karya Maju larger than Cooperation Tandan Mas Jaya and larger than Cooperation Tunas Muda. Cooperation Tandan Mas Jaya has accounts receivable turnover, average days of collection of receivables, inventory turnover and average days of inventory stored more active than Cooperation Karya Maju and more active than Cooperation Tunas Muda. While the working capital turnover of Cooperation Karya Maju is more active than Cooperation Tandan Mas Jaya and more active than Cooperation Tunas Muda. Key word: Financial performance, financial ratio